Portable Power Supply with Ultraeapacitor Application - ABDUL HAMID, MOHAMAD NOR AKMAL (Universiti Teknologi PETRONAS, 2009)
Portable power supply reqmres a means of storing energy for powering applications. Energy storage is typically limited to alk:aline or rechargeable batteries. In either instance, the batteries require replacing or recharging.